PARTICIPATION OF FINANCIAL INSTITUTIONS IN THE DEVELOPMENT OF NURUL ABROR AL-ROBBANIYIN ISLAMIC BOARDING SCHOOL - Nur Wulandari (Assets Journal: Journal of Economic and Business, 2023)
This research shows that in addition to being able to help people in need by providing financing, Islamic boarding school financial institutions play a role in improving the development of Islamic boarding schools. Islamic boarding schools which are centers of education require funds for their development, one of which is infrastructure development so that educational facilities can be well received by students who aim to support students' learning at Islamic boarding schools. Efforts to have financial institutions are expected to be a solution in developing infrastructure at the Nurul Abror Al Robbaniyyin Islamic Boarding School which is the locus in this research.